PENGGUNAAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KOMPETENSI BELAJAR MATEMATIKA SISWA MATERI BANGUN RUANG SISI LENGKUNG - DIANA SYARIFAH (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2022)
This study aims to describe the level of competence of learning outcomes in learning mathematics with the material of Constructing Curved Side Space by using the Discovery Learning learning model in class IX B students of SMP Negeri 16 semester II (two) for the 2020/2021 academic year. The problem that is the subject of discussion is whether through the Discovery Learning model can improve competence in learning to construct curved side spaces for class IX B SMP Negeri 16 second semester of the 2020/2021 academic year? The research method is in the form of Classroom Action Research (CAR) with 2 cycles, each cycle includes 4 stages, namely planning, action, observation and reflection. Data collection techniques are tests and observations with data collection tools in the form of written test questions and observation sheets which are validated by data through triangulation. The results of the study showed that the competence of learning outcomes in mathematics with curved side spaces for class IX B SMP Negeri 16 second semester of the 2020/2021 academic year increased from an average of 68.84 with 9 students or 26.47% in the pre-cycle to an average of 70. with 19 students or 55.88% in the first cycle and the second cycle to an average of 76 with 29 students or 85.29% complete the KKM. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan tingkat kompetensi hasil belajar dalam pembelajaran matematika materi Bangun Ruang Sisi Lengkung dengan menggunakan model pembelajaran Discovery Learning pada siswa kelas IX B SMP Negeri 16 semester II (dua) tahun pelajaran 2020/2021. Permasalahan yang menjadi pokok bahasan adalah apakah melalui model Discovery Learning dapat meningkatkan kompetensi dalam pembelajaran bangun ruang sisi lengkung siswa kelas IX B SMP Negeri 16 semester dua tahun pelajaran 2020/2021?. Metode penelitian berupa Penelitian Tindakan Kelas (PTK) dengan 2 siklus, masing- masing siklus meliputi 4 tahap yaitu perencanaan, tindakan, pengamatan dan refleksi. Teknik pengumpulan data dengan tes dan observasi dengan alat pengumpulan data berupa soal tes tulis dan lembar observasi yang divalidasi data melalui triangulasi. Hasil penelitian menunjukkan kompetensi hasil belajar matematika materi bangun ruang sisi lengkung siswa kelas IX B SMP Negeri 16 semester dua tahun pelajaran 2020/2021 meningkat dari rata-rata 68,84 dengan 9 siswa atau 26,47% pada pra siklus menjadi rata-rata 70 dengan 19 siswa atau 55,88% pada siklus I dan siklus II menjadi rata-rata 76 dengan 29 siswa atau 85,29% tuntas KKM.